Teaching, Enacting, and Sustaining Hope in the Shadow of COVID-19 - Stitzlein, Sarah (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
This article extends initial ideas on what hope is, why it matters to democracy, and how to teach it in schools, which were first presented by Sarah M. Stitzlein in her book Learning How to Hope: Reviving Democracy through Our Schools and Civil Society (Oxford University Press, 2020). It accounts for recent obstacles to hope, especially the impact of the COVID-19 pandemic. It suggests ways that other philosophers of education might further pursue describing and cultivating hope in light of recent social, political, economic, and health obstacles due to the pandemic. It emphasizes the role of inquiry and problem-solving using pragmatist philosophical approaches.